Learning by Observing: Information Spillovers in the Execution and Valuation of Commercial Bank M&As - DELONG, GAYLE; DEYOUNG, ROBERT (Journal of Finance, 2007)
ABSTRACT We offer a new explanation for why academic studies typically fail to find value creation in bank mergers. Our conjectures are predicated on the idea that, until recently, large bank acquisitions were a new phenomenon, with no best practices history to inform bank managers or market investors. We hypothesize that merging banks, and investors pricing bank mergers, learn by observing information that spills over from previous bank mergers. We find evidence consistent with these conjectures for 216 M&As of large, publicly traded U.S. commercial banks between 1987 and 1999. Our findings are consistent with semistrong stock market efficiency.